Analysis Of The Influence Of Managerial Ownership, Organization Size, Debt Contracts And Information Systems On Manufacturing Company Accounting Systems - Imam Hanafi; Asri Ady Bakri; Tanti Widia Nurdiani; Samuel PD Anantadjaya; Hartono (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study examines manufacturing businesses listed on the Indonesia Stock Exchange between 2020 and 2022 in order to ascertain the impact of managerial ownership, knowledge asymmetry, loan contracts, and company size on accounting conservatism. 34 businesses were utilized as a sample in this study. Purposive sampling was the method of sampling employed in this investigation. Multiple regression analysis was used in this study to evaluate the hypothesis. The findings demonstrated a substantial relationship between management ownership and accounting conservatism. Accounting conservatism is significantly impacted by contract debt. Accounting conservatism is significantly influenced by company size. While accounting conservatism is unaffected by information asymmetry. Accounting conservatism as assessed by BTMR is influenced by managerial ownership, knowledge asymmetry, debt obligations, and firm size collectively.